Remembering the 1936-37 UAW-GM sit-down strike: stratification of a UAW member's identity in Sitdowners Memorial Park - Keel, Aaron, author; Anderson, Karrin Vasby, advisor; Dickinson, Greg, committee member; Kirkland, Kenneth J., committee member (Colorado State University. Libraries, 2011)
In 1937, the United Automobile Workers (UAW) won recognition from General Motors (GM) through the historic sit-down strike in Flint, Michigan. This strike marked the beginning of the labor movement and the battle for worker's rights that is continuing into the present day. Sitdowners Memorial Park (SMP), located in Flint, remembers and commemorates the striker's great achievements in 1937. It is also a place where citizens encounter compelling narratives of the past, pay tribute to those who have come before them, build community, negotiate identity, and receive instruction for the present and future. In this thesis, I explore SMP as an experiential landscape. In exploring the park, I answer two questions. First, how does SMP construct a UAW member's identity? Second, how does SMP represent female gender roles and, more specifically, what kind of agency is attributed to women as members of the UAW in this counterpublic space? I argue that SMP enlists memories of the sit-down strike and its impacts on society to reinvigorate a dying community and offer visitors rhetorical resources justifying pro-union perspectives. In doing so, a counterpublic identity is created. In establishing a UAW member's identity as counterpublic, still fighting for recognition from the larger public, SMP also reinforces the worker/homemaker double bind that is prevalent as part of many women workers' historical and contemporary lived experience. This double bind can inhibit female workers' agency within the counterpublic space of the UAW where they can occupy a "counterprivate" space. Today, however, through the corrections and additions to the park over time, female workers are granted agency, but they are reminded that their participation in the public comes at a cost; the double bind continues to discipline them. Ultimately, SMP works to educate its visitors on the progress that the UAW has attained and the social significance of the sit-down strike. Through this education and remembering, SMP advocates that a visitor to the park must work to maintain what was won in 1937 and participate in a pro-union fight by carrying on the strikers' tradition of progressive politics.
Keywords: memory; GM; identity; public sphere; strike; UAW